Assessment and Performance Analysis of Machine Learning Techniques for Gas Sensing E-nose Systems - Mahmood, Lubna Syeda (2021)
A Master of Science thesis in Engineering Systems Management by Lubna Syeda Mahmood entitled, “Assessment and Performance Analysis of Machine Learning Techniques for Gas Sensing E-nose Systems”, submitted in November 2021. Thesis advisor is Dr. Zied Bahroun and thesis co-advisor is Dr. Mehdi Ghommem. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).